EKSPLORASI KERAGAMAN BURUNG DAN CAPUNG SEBAGAI BIO-INDIKATOR LINGKUNGAN PERTAMBANGAN - Dian Iswandaru; Hendry Micky; Novitasari; Aniessa Rinny Asnaning; Sepnina Like Lestari; Tugiyono; Syamsurijal Rasimeng; Jujur Prasetyo (Jurnal Nusa Sylva, 2026)
Birds and dragonflies are two taxonomic groups with high potential as environmental bioindicators, particularly in andesite mining areas. Both groups are highly responsive to changes in terrestrial and aquatic environments. This study aimed to explore the species diversity of birds and dragonflies in a mining environment as a database for environmental management and biodiversity conservation efforts. Bird data were collected using the point count method, while dragonfly data were obtained through an exploratory method with purposive sampling. The results recorded 10 bird species from 7 families, namely Alcedinidae, Estrildidae, Campephagidae, Columbidae, Cuculidae, Rallidae, and Pycnonotidae, as well as 6 dragonfly species from 1 family, Libellulidae. The bioecological index of birds and dragonflies is categorized as medium for diversity index (H'), low for richness index (R), high for evenness index (E), and low for dominance index (C). The bird feeding guilds are dominated by granivores, omnivores, insectivores (30% each), and frugivores (10%). All birds and dragonflies are of Least Concern (LC), Non-Appendix (NA) status and are not protected. The presence of birds and dragonflies indicates that the andesite mining exploration area still functions ecologically as a habitat for these taxa, despite experiencing moderate levels of environmental pressure. All recorded species belong to generalist groups that are relatively tolerant of disturbance and pressure from anthropogenic activities, particularly mining. Repeated population surveys (monitoring) of birds and dragonflies, along with a strong commitment to maintaining protected areas for these taxa within the mining scope, are necessary to support biodiversity conservation